Joseph Chamberlain and South Africa - Marsh, Peter (My University, 1983)
The most remarkable feature of Joseph Chamberlains government of the Empire was his attempt to command assent at home and abroad. At home he was extraordinarily successful. His complicity in the Jameson Raid and his responsibility for the long, expensive and no more than marginally successful war with the South African republics made that achievement only the more remarkable. But abroad, particularly in South Africa, success eluded him. That lack of success raised questions about the worth of his whole imperial enterprise, questions to which most people now, historians and laymen alike, would give the same negative answer. Conscious of the risk of failure though equally confident of the possibility of success, Chamberlain concentrated his final energies on an attempt to harness domestic and colonial economic self-interest to the chariot of the Empire, This time success eluded him at home, though he might have been able to turn the tide there if fate had allowed him the same vigorous old age that Gladstone and later Churchill enjoyed. But this part of Chamberlain's story lies outside my concern in this essay. What I want to suggest here is the liberal as well as authoritarian character of his leadership of the Empire particularly in South Africa during his tenure as Colonial Secretary.
African Studies Seminar series. Paper presented 4 August 1983
Keywords: Chamberlain, Joseph. 1836-1914; South Africa. History. 1836-1909